Revitalizing Samin Ethics For Character Building In Climate Change Education - Khoirul Huda (Proceeding International Conference on Digital Education and Social Science, 2024)
The purpose of the research is to reconstruct the ethical values of the life of the Samin tribe which has the potential to form a resilient cultural attitude amid the development of climate change. The Samin tribe as a local community that until now still maintains noble values. This positions it as the inheritor of genealogical values so as to encourage wise actions. Although considered a minority, the unique scope of ethical values can be internalized in the field of education. The ethnographic method was used in this research through interview techniques, observation and document analysis. This approach is able to guarantee understanding in interpreting the way of action of the Samin tribe. Their ethical values are relevant to respond to the phenomenon of competence, especially for students who are subject to the impacts of climate change in Indonesia. Samin ethical teachings are embodied in the portrait of jatmika science. The science of jatmika harmonizes the body and soul in ethics. The ethics effectively shape students to gain asceticism competence in carrying out actions. The competence of asceticism is an asset to protect quality character.